Modelling of Critical Velocities of the Cardan Mechanism using Transfer Matrix Method - Petr Hrubý; Tomáš Náhlík (Communications - Scientific letters of the University of Zilina, 2021)
The presented paper focuses to rotating components of mechanical constructions. The problem of the spatial combined bending-gyratory vibration and calculation of the Eigen frequencies is studied. The model of Cardan Mechanism is solved by the transfer matrix method. Transfer matrices were derived for shaft, concentrated mass and elastic bearing. The physical and mechanical properties of each part of the mechanism are hidden in these matrices. A procedure for calculating Eigen frequencies was proposed.